COFFEE CERTIFICATION PARTICIPATION AND ITS IMPACT ON SMALLHOLDER FARMERS’ INCOME IN JIMMA ZONE, SOUTHWESTERN ETHIOPIA - Yadeta Bekele Bekere; Guta Regasa Megersa (Socio-Economics/Agribusiness Department, 2021)
Certification is an instrument to add value to a product, and it addresses a growing worldwide demand for healthier and more socially and environmentally friendly products. Globally, coffee certification has received strong recognition as it is proved to increase smallholder farmers’ access to input and output markets, production, productivity and income. This study investigates the major determinants of coffee certification participation. It also analyzes the welfare gains of participation in the certification schemes by smallholder coffee growers. Both primary and secondary data were used. Primary data were collected from randomly selected 247 coffee producers. Structured questionnaires, focus group discussions and key informant interviews were employed to collect the primary data. Descriptive statistics and econometric models were used for data analysis. Probit model was used to identify factors affecting participation in coffee certification schemes. Propensity score matching technique was used to estimate the impact of coffee certification participation on smallholders’ annual revenue from coffee production. The probit model result revealed that access to training, family size, land size owned, experience in coffee production, education status were significantly determined the smallholders farmers’ participation decision in coffee certification. The propensity score matching model result also shows that participation in coffee certification significantly (p=0.001) improved farmers’ annual revenue by 2,902 Ethiopian birr compared to selling coffee without the certification schemes. This income impact is mainly attributed to the premium price the certification offer to farmers for high quality coffee. Therefore, policies or projects related to coffee value chains should target improving farmers’ access to training, boosting the access to education, working on farmers’ productivity and increasing their technical knowhow on coffee certification to increase farmers’ participation in coffee certification and to improve their annual revenue earning level in the study area.